An updated network meta-analysis of non-pharmacological interventions for primary hypertension in adults: insights from recent studies - Ziwen Chen; Qifu Li; Tao Xu; Xueli Zhou; Yunjie Shu; Taipin Guo; Fanrong Liang (Systematic Reviews)
Abstract Background Primary hypertension significantly impacts global cardiovascular health, contributing to increased mortality rates and posing a substantial public health challenge. Recognizing the growing evidence supporting non-pharmacological interventions (NPIs) for controlling primary hypertension, our study employs Network Meta-Analysis (NMA) to comprehensively assess their efficacy. Methods This review updates a prior systematic review by searching for original literature on NPIs for primary hypertension from 2013 to 2024. We conducted a thorough search in eight databases, including PubMed, Embase, Web of Science, Cochrane Central Register of Controlled Trials, Allied and Complementary Medicine Database, CNKI, WanFang Data, and Chongqing VIP, identifying potential randomized controlled trials (RCTs) from January 1, 2013, to August 1, 2024. Primary outcomes included the mean changes in blood pressure before and after treatment. Analysis was performed using GeMTC package (R 4.2.3), and Stata 17.0. The confidence of evidence was examined using Confidence in Network Meta-Analysis (CINeMA). Results Utilizing NMA, we reviewed 9,189 studies, identifying 54 eligible articles with 5,827 participants. Investigating 22 distinct NPIs, the focus was on changes in systolic and diastolic blood pressure pre and post-treatment. Lifestyle intervention + Tai Chi significantly reduced systolic (-21.75 mm Hg; 95% CI -33.25 to -10.02) and diastolic blood pressure (-13.62 mm Hg; 95% CI -23.14 to -3.71) compared to usual care and other NPIs. Consistency and regression analyses did not reveal significant differences. Conclusion This review provides a comprehensive evaluation of NPIs for primary hypertension, emphasizing lifestyle + Tai Chi as a preferred NPI. Breathing exercises show potential in lowering systolic blood pressure, and acupuncture + tui na demonstrates effectiveness in reducing diastolic blood pressure, outperforming other interventions. The study reinforces the role of NPIs in managing primary hypertension, providing a foundation for future hypertension research.